Two chiral haloplumbate hybrids with thermochromism luminescence and application potential as luminescent thermometers. Issue 46 (10th November 2020) - Yu, Shan-Shan; Zhao, Hai-Rong; Zhang, Hui; Duan, Hai-Bao
Abstract : Two chiral hybrids exhibit dual emission and luminescence thermochromism properties, and they hold great potential for use as self-referenced luminescent thermometers. Abstract : Two noncentrosymmetric haloplumbate hybrids, [C6 H10 (NH3 )2 ][PbCl4 ] (1 ) and [C6 H10 (NH3 )2 ][PbBr4 ] (2 ), have been synthesized. Crystals of 1 and 2 belong to the chiral space group P 21 21 21 . The inorganic parts comprise a one-dimensional chain structure for 1 and a two-dimensional sheet structure for 2 . Both compounds exhibit thermochromic luminescence originating from dual emission and have potential applications as self-referencing luminescent thermometers.